Financial Awareness and Attitudes Toward Money: Empirical Evidence from Indonesia - Wendy, Wendy (Equator Journal of Management and Entrepreneurship (EJME), 2026)
Attitudes toward money remain comparatively underexplored in the behavioral finance literature, particularly in studies that examine multiple determinants within a single integrated framework. To address this gap, this study develops and empirically tests an integrated model using survey data from 260 respondents in Indonesia. Five regression models were estimated to examine the effects of five predictors, one moderating variable, and one control variable. The findings indicate that financial self-efficacy, financial awareness, and reference groups are positively associated with attitudes toward money. Furthermore, moderation analyses identify income as a pure moderator of the effects of reference groups, media role, and perceived risk on attitudes toward money. The inclusion of gender across all model specifications does not alter the main findings, confirming the robustness of the estimated models.